Influence of vegetable oils and their constituents on in vitro human keratinocyte and fibroblast proliferation and migration - Nina Poljšak; Nina Kočevar Glavač; Matjaž Ravnikar; Matjaž Jeras (Scientific Reports)
Abstract Human skin is a complex organ essential for protection, hydration and regeneration, with keratinocytes and fibroblasts playing pivotal roles in wound healing and tissue renewal. This study investigates the effects of selected vegetable oils, fatty acids and unsaponifiable compounds on the proliferation and migration of human keratinocytes and fibroblasts in vitro. Oils were selected based on their specific fatty acid profiles, including coconut, olive, linden, poppy, pomegranate, marigold and linseed oils. Using cell proliferation and gap closure assays, the impact of these oils and their constituents on cell proliferation and migration was evaluated. Results showed that the tested biological activity of the oils depended primarily on the fatty acid composition of their triglycerides. Oils rich in essential fatty acids, particularly linoleic acid, significantly promoted cell proliferation. In contrast, unsaponifiable compounds showed no effect, while punicic acid and pomegranate seed oil had a significant negative impact. The oils did not exert notable effects on the closure rate of the artificial wound gap; however, sterculic and oleic acids inhibited gap closure and induced changes in cell morphology. These findings support the role of plant oils and their composition in enhancing skin cell regeneration, and provide in vitro evidence to support their application in cosmetic and dermatological formulations aimed at skin repair and evidence-based skincare.